Penyuluhan Tentang Penyakit Usus Buntu di kalangan Mahasiswa - Chafia azalia (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The World Health Organization (WHO) reports that appendicitis is the eighth leading cause of death in the world in 2020 and is estimated to be the fifth leading cause of death in the world in 2021 (Efendi, 2015). The incidence of appendicitis is more common in developing countries than developing countries, this is due to changes in dietary patterns in developed countries towards low fiber foods.Appendicitis (appendicitis) is a gastrointestinal disease and surgical disease that often occurs in society, especially among teenagers such as students. Young people tend to have poor fiber intake, for example not eating enough vegetables and fruit, which causes functional blockage of the appendix and increases bacterial growth. This can cause appendicitis. Amanah Modern Islamic College-Tahfiz Quran High School Jalan Captain Sumarsono No. used to organize those social services. 180, Helvetia Village, Medan Sunggal District, Deli Serdang Regency, North Sumatra. The target of the activity is students from the Amanah Modern Islamic High School-Tahfiz Qur'an Middle School. The results of this community service have a positive impact on the parties involved, especially the students of Amanah Modern Islamic High School-Tahfiz Qur'an Middle School. Students can increase their knowledge about preventing appendicitis in teenagers. In addition, students can improve skills in preventing appendicitis in teenagers by trying to consume high fiber such as vegetables and fruit to prevent appendicitis.